The development of wing shape in Lepidoptera: mitotic density, not orientation, is the primary determinant of shape. Issue 2 (March 2014) - Nijhout, H. Frederik; Cinderella, Margaret; Grunert, Laura W.
SUMMARY The wings of butterflies and moths develop from imaginal disks whose structure is always congruent with the final adult wing. It is therefore possible to map every point on the imaginal disk to a location on the adult wing throughout ontogeny. We studied the growth patterns of the wings of two distantly related species with very different adult wing shapes, Junonia coenia and Manduca sexta. The shape of the wing disks change throughout their growth phase in a species‐specific pattern. We measured mitotic densities and mitotic orientation in successive stages of wing development approximately one cell division apart. Cell proliferation was spatially patterned, and the density of mitoses was highly correlated with local growth. Unlike other systems in which the direction of mitoses has been viewed as the primary determinant of directional growth, we found that in these two species the direction of growth was only weakly correlated with the orientation of mitoses. Directional growth appears to be imposed by a constantly changing spatial pattern of cell division coupled with a weak bias in the orientation of cell division. Because growth and cell division in imaginal disk require ecdysone and insulin signaling, the changing spatial pattern of cell division may due to a changing pattern of expression of receptors or downstream elements in the signaling pathways for one or both of these hormones. Evolution of wing shape comes about by changes in the progression of spatial patterns of cell division.